2009
DOI: 10.1007/s00382-009-0537-4
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of snow condition trends to future ground climate

Abstract: Global climate models predict that terrestrial northern high-latitude snow conditions will change substantially over the twenty-first century. Results from a Community Climate System Model simulation of twentieth and twenty-first (SRES A1B scenario) century climate show increased winter snowfall (?10-40%), altered maximum snow depth (-5 ± 6 cm), and a shortened snow-season (-14 ± 7 days in spring, ?20 ± 9 days in autumn). By conducting a series of prescribed snow experiments with the Community Land Model, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
149
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 27 publications
4
149
0
Order By: Relevance
“…The timing and magnitude of snowfall, the resulting snow depth, and the length of the snow season (the number of days with a significant snow pack on the ground) are some of the most important factors influencing the response of soil temperature to variations in air temperature (Stieglitz et al, 2003;Zhang et al, 2008a;Jorgenson et al, 2010;Lawrence and Slater, 2010) and therefore ultimately impact biogeochemical cycling rates in the soil (Schimel et al, 2004). Lawrence and Slater (2010) estimate that 50-100 % of the soil temperature changes by the end of the last century could be caused by variations in the snow state.…”
Section: Snowmentioning
confidence: 99%
See 3 more Smart Citations
“…The timing and magnitude of snowfall, the resulting snow depth, and the length of the snow season (the number of days with a significant snow pack on the ground) are some of the most important factors influencing the response of soil temperature to variations in air temperature (Stieglitz et al, 2003;Zhang et al, 2008a;Jorgenson et al, 2010;Lawrence and Slater, 2010) and therefore ultimately impact biogeochemical cycling rates in the soil (Schimel et al, 2004). Lawrence and Slater (2010) estimate that 50-100 % of the soil temperature changes by the end of the last century could be caused by variations in the snow state.…”
Section: Snowmentioning
confidence: 99%
“…Lawrence and Slater (2010) estimate that 50-100 % of the soil temperature changes by the end of the last century could be caused by variations in the snow state.…”
Section: Snowmentioning
confidence: 99%
See 2 more Smart Citations
“…(ii) Hall and Qu (2006) and Fletcher et al (2012) have shown this feedback to be correctly represented only in a minority of the CMIP3 (Coupled Model Intercomparison Project -Phase 3: http://www-pcmdi.llnl.gov/ ipcc/about ipcc.php) models. Due to its low heat conductivity, snow also effectively insulates the underlying soil, with important effects on deep soil temperatures and permafrost extent (Zhang, 2005;Lawrence and Slater, 2010;Gouttevin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%